Concept Analysis of the Tarbiyatul AulÄd FÄ« Al-IslÄm Abdullah Nashih Ulwan: Children's Social Education Paying Attention to the Rights of Others in Forming Independent Character - Almuhajir, Almuhajir (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This study aims to explain the concept of children's social education responsibility from the perspective of Abdullah Nashih Ulwan, which is focused on analyzing the material by paying attention to the rights of others to form children's independent character. This type of research is non-interactive qualitative with a concept analysis approach. The results showed that there are six concepts of children's social education responsibility in paying attention to the rights of others to form an independent character according to Abdullah Nasih Ulwan. First, the rights of both parents, namely to introduce the rights of both parents to their children by being filial to them. Second, sibling rights, namely the rights of people who have lineage or kinship. Third, the right of neighbours, namely all people next to their house on the right, left front, and back, about forty houses. Fourth, the teacher's right, namely to educate children to respect the teacher, be reluctant to him, and fulfil the teacher's rights. Fifth, the rights of friends, namely choosing friends who are faithful and pious for their children. Sixth, the rights of older people, namely the rights of people who are older, have more knowledge, have higher piety and religion, and are more dignified, noble and have status.